Autophagy in airway diseases: a new frontier in human asthma?. Issue 1 (20th October 2015) - Zeki, A. A.; Yeganeh, B.; Kenyon, N. J.; Post, M.; Ghavami, S.
Abstract: The study of autophagy ('self‐eating'), a fundamental cell fate pathway involved in physiological and pathological subcellular processes, opens a new frontier in the continuous search for novel therapies for human asthma. Asthma is a complex syndrome with different disease phenotypes. Autophagy plays a central role in cell physiology, energy and metabolism, and cell survival. Autophagy's hallmark is the formation of double‐membrane autophagic autophagosomes, and this process is operational in airway epithelial and mesenchymal cells in asthma. Genetic associations between autophagy genes and asthma have been observed including single nucleotide polymorphisms in Atg5 which correlate with reduced lung function. Immune mechanisms important in asthma such as Th2 cells and eosinophils also manifest autophagy. Lastly, we address the role of autophagy in extracellular matrix deposition and fibrosis in asthmatic airways remodeling, a pathologic process still without effective therapy, and discuss potential pharmacologic inhibitors. We end by offering two opposing but plausible hypotheses as to how autophagy may be directly involved in airway fibrosis.